SIMULATION OF PRECISION ATTITUDE AND HEADING REFERENCE SYSTEM PERTURBED BY ENVIRONMENTAL DISTURBANCES - Sushchenko, Olha (Proceedings of National Aviation University (archive), 2017)
Purpose: The paper focuses on problems of simulation of perturbed robust precision attitude and heading reference systems, which can be applied in navigation of marine vehicles. The main goal is to create the mathematical model adapted to simulation of the perturbed system and models of the environmental disturbances. Methods: To solve the given problem the methods of the robust control system theory, filtration theory and probability theory are used. Results: The model of the perturbed attitude and heading reference system created by means of Simulink is given. The expression for the disturbance moment is proposed. Analysis of possible environmental disturbances for a system of the considered type has been done. Models of environmental disturbances based on the filtration theory are obtained. Comparison of two approaches to development of models of environmental disturbances is carried out. Conclusions: The results of simulation of the precision attitude and heading reference system taking into consideration environmental disturbances are represented. Obtained results can be useful for design of precision navigation systems of the moving vehicles.